Buffalo Bill Cody, a man of the west - Ingraham, Prentiss, 1843-1904 (University Press of Kansas, 2019)
"In 1895-6, Hugh Wetmore, Buffalo Bill Cody's brother-in-law and editor of the Duluth (Wisconsin) Press, serialized a Cody biography by Prentiss Ingraham. A prolific dime novelist, Ingraham was also an unabashed fan of Cody; his nearly 600 novels frequently featured sensationalized Cody heroics. Cody could do nothing wrong or embarrassing and was never anything but cooperative, kind, and thoughtful of others. When Cody confessed to questionable actions, Ingraham either eliminated them or amended them to negate any connotation of imperfection. While many dime novels and biographies of Cody have been published and republished, many in scholarly editions, Ingraham's work has never been published in book form. Cody scholar Sandra Sagala has transcribed and edited the text of the biography from the original, and provided an introduction and footnotes. Several line drawings by a contemporary artist accompany the text."--Provided by publisher.